Transvaginal mesh in Australia: An analysis of news media reporting from 1996 to 2021 - Mina Motamedi; Stacy M. Carter; Chris Degeling (Wiley, 2023)
Abstract Introduction Transvaginal mesh (mesh) surgeries have been used to treat stress urinary incontinence (incontinence) and/or pelvic organ prolapse (prolapse). In Australia, as in many other countries, the harms caused by mesh eventually prompted individual and collective attempts to achieve redress. The rise of mesh surgery as a procedure, the experience of mesh‐affected women and the formal inquiries and legal actions that followed all occurred in social, cultural and discursive contexts. One strategy to understand these contexts is to track how the mesh and key actors in the mesh stories have been portrayed in mass media sources. We conducted a media analysis of the most highly read Australian newspapers and online news media platforms, focusing on how mesh and the interaction of stakeholders in mesh stories were presented to the Australian public. Method We searched systematically in the top 10 most‐read print and online media outlets in Australia. We included all articles that mentioned mesh, from the date of first use of mesh in Australia to the date of our final search (1996-2021). Result After early scant media reporting focusing on the benefits of mesh procedures, major Australian medicolegal processes created a hook to shift reporting about mesh. The news media then played a significant role in redressing women's experienced epistemic injustice, including by amplifying previously ignored evidence of harm. This created an opportunity for previously unreported suffering to be revealed to powerful actors, in settings beyond the immediate control and epistemic authority of healthcare stakeholders, validating women's testimony and creating new hermeneutic resources for understanding mesh. Over time, media reports show healthcare stakeholders responding sympathetically to these new understandings in public discourse, contrasting with their statements in earlier media coverage. Conclusion We argue that mass media reporting, in synergy with medicolegal actions and the Australian Senate Inquiry, appears to have provided women with greater epistemic justice, giving their testimony privileged epistemic status such that it was considered by powerful actors. Although medical reporting is not recognised in the hierarchy of evidence embedded in the medical knowledge system, in this case, media reporting appears to have contributed to shaping medical knowledge in significant ways. Patient or Public Contribution We used publicly available data, print and online media outlets, for our analysis. Therefore, this manuscript does not contain the direct contribution of patients, service users, caregivers, people with lived experience or members of the public.